Learning Words and Definitions in Two Languages: What Promotes Cross‐Language Transfer?. Issue 1 (6th December 2017) - Pham, Giang; Donovan, Danaee; Dam, Quynh; Contant, Amy
Abstract: This study used a brief vocabulary training paradigm to examine two factors for cross‐language transfer: how similar the first language (L1) is to the second language (L2) and L1‐L2 proficiency levels. Fifty‐four sequential bilingual children (aged 6–8) with similar L2 English proficiency levels were assigned to three equal groups: a Vietnamese‐English group with low L1 proficiency, a Spanish‐English group with low L1 proficiency, and a Spanish‐English group with high L1 proficiency. Individual training consisted of two mediated learning experiences conducted in the L1 targeting eight vocabulary items using narrative‐based activities. Four of eight target words were cognates between Spanish and English. Pre‐ and posttesting measured definition quality in the L1 and L2. All groups showed improvement in the L1 following training, but only the Spanish‐English group with high L1 proficiency improved in L2 English, revealing a degree of spontaneous cross‐language transfer among children with high L1‐L2 proficiency. Open Practices: This article has been awarded an Open Materials badge. Study materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .